Income smoothing and market performance: empirical study on manufacturing companies listed in Indonesia stock exchange - Kencana Dewi; Mukhtaruddin; Iqbal Agung Prayudha (Investment Management & Financial Innovations, 2018)
In the age of modern accounting, the era where income information is viewed to be no longer the main information that investor seeks, income smoothing is proven to be still existing. This study aims to find why income smoothing (IS) still exists in Indonesia Stock Exchange (IDX) by analyzing its effect on the market performance (MP). The study divides MP into three perspectives: market response is representing current investor; market risk (MR) is representing potential investor; and market value (MV) is representing the management. Purposive sampling method is applied in this study and 65 companies are examined throughout 2011–2013.Using three models to analyze each of the relation, the results shows that IS only significantly affects the MP of companies in the aspect of market response, while the other aspects, MR and MV, yield insignificant results.